THE ROLE OF SOCIAL PROTECTION IN THE NEW DEVELOPMENT STRATEGY OF UZBEKISTAN - Djurakulovich Ziyadullaev Makhmudjon (Scholar Express Journals, 2022)
This article highlights the ongoing reforms in the field of social security in the Republic of Uzbekistan, the constitutional consolidation of the rights of the population to social security, the existing problems and ways to solve them in the coming years.It is also noted that one of the seven priority areas identified in the "new development strategy of Uzbekistan for 2022-2026", developed on the principle of "from an action strategy to a development strategy", is the implementation of a fair social policy, the development of human capital, as well as the implementation of reforms implemented after 2017, including by appointment and the payment of pensions, methods have been affected.
Keywords: pension; compensation; payment; bank plastic cards; disabled person; social security